PENGARUH PEMBELAJARAN CREATESEM BERVISI SETS TERHADAP PENCAPAIAN KOMPETENSI BUFFER DAN HIDROLISIS GARAM - Maesyaroh, Ida; Binadj, Achmad; Cahyono, Edy (Universitas Negeri Semarang, 2013)
The main problem in learning today is the low of students’ understanding. It is caused by students that are not actively in learning process. On School Based Curriculum, the learning process requires students to take apart in active teaching learning. The aim of this study is to know whether using CREATESEM SETS visionary give positive effect on competence achievement related to the buffer solution and the salt hydrolysis. The research was conducted in SMA Negeri 2 Pati. Purposive sampling was used in this study and class XI-6 as an experimental class got treatment CREATESEM SETS visionary, while class XI-7 as control class got a different treatment, treated by using SETS visionary of learning. The design of this study was control group pretest posttest. The data were collected by using test method, documentation, observation, and questionnaires. The results showed a classical completeness of experimental class was 88%, meanwhile for control class was 56%. The mean value of the psychomotor aspects of the experimental class was 85% better than control class that was 82%.The mean value of the affective aspects of the experimental class students was 85% better than control class that was 83%. So, using CREATESEM SETS visionary in teaching learning had positive impact 31% on achievement of students’ competence related to the buffer solution and the salt hydrolysis